Quantitative analysis of superb microvascular imaging for monitoring tumor response to chemoradiotherapy in locally advanced cervical cancer - Zhu, Yi; Tang, Yixin; Zhang, Guonan; Zhang, Jie; Li, Yanjie; Jiang, Zhuolin (Frontiers in Oncology, 2023)
Objectives: As an ultrasound image processing method, superb microvascular imaging (SMI) extracts and visualizes flow signals from vessels through advanced clutter suppression technology. We investigated the feasibility of SMI in monitoring treatment response in patients with locally advanced cervical cancer (LACC) undergoing chemoradiotherapy (CRT). Methods: Forty-nine patients underwent CRT and received SMI examination at 3 time points: before therapy (baseline), 3 weeks during, and 1 month after CRT. The maximum tumor diameter (Dmax), vascularity index (VI), and their percentage changes (ΔDmax and ΔVI) were calculated. ΔDmax was compared with MRI results as the reference standard. Results: Based on the MRI findings, 44 were classified as complete response (CR) group and 5 as partial response (PR) group. The Dmax and ΔDmax showed decrease in CR and PR groups at 3 weeks during CRT (P < 0.05), but no significant difference between the two groups (P > 0.05). Compared to the baseline, significant decrease in VI and ΔVI were observed at during and after treatment in the two groups (P < 0.05). Moreover, there were significant differences in VI and ΔVI at 3 weeks during CRT between the CR and PR groups (P < 0.05). ΔVI at 3 weeks during CRT showed a better predictive performance for responder prognosis than VI (AUC = 0.964, AUC = 0.950, respectively, P = 0.001), with a cut-off value of 41.6% yielding 100% sensitivity and 86.4% specificity. Conclusions: The SMI parameters (VI and ΔVI) have potential for monitoring treatment response in LACC.